Hemodialysis Procedures for Stable Incident and Prevalent Patients Optimize Hemodynamic Stability, Dialysis Dose, Electrolytes, and Fluid Balance - Stuard, Stefano; Ridel, Christophe; Cioffi, Mario; Trost-Rupnik, Alijana; Gurevich, Konstantin; Bojic, Marija; Karibayev, Yerkebulan; Mohebbi, Nilufar; Marcinkowski, Wojciech; Kupres, Vlasta; Maslovaric, Jelena; Antebi, Alon; et al. (Journal of clinical medicine, 2024)
The demographic profile of patients transitioning from chronic kidney disease to kidney replacement therapy is changing, with a higher prevalence of aging patients with multiple comorbidities such as diabetes mellitus and heart failure. Cardiovascular disease remains the leading cause of mortality in this population, exacerbated by the cardiovascular stress imposed by the HD procedure. The first year after transitioning to hemodialysis is associated with increased risks of hospitalization and mortality, particularly within the first 90-120 days, with greater vulnerability observed among the elderly. Based on data from clinics in Fresenius Medical Care Europe, Middle East, and Africa NephroCare, this review aims to optimize hemodialysis procedures to reduce mortality risk in stable incident and prevalent patients. It addresses critical aspects such as treatment duration, frequency, choice of dialysis membrane, dialysate composition, blood and dialysate flow rates, electrolyte composition, temperature control, target weight management, dialysis adequacy, and additional protocols, with a focus on mitigating prevalent intradialytic complications, particularly intradialytic hypotension prevention.
Keywords: hemodialysis procedures; dialysis electrolyte balance; dialysis dose; dialysis fluid balance; hemodynamic stability